Chemical analysis of different larval instars and tissues of Pachycondyla (=Neoponera) villosa (Hymenoptera: Formicidae, Ponerinae) - Zara, Fernando José [UNESP]; Cabrera, Aivlé Cecilia [UNESP]; Jaffé, Klaus [UNESP]; Caetano, Flávio Henrique [UNESP] (My University, 2002)
Chemical analyses of complete larvae of the first to third instar and cuticle, fat body and salivary glands extracts of fourth instar larvae using gas chromatography and gas chromatography-mass spectrometry, were performed upon Pachycondyla villosa. The results revealed that P. villosa larvae do not produce a pheromone, as only fatty acids and n-alkanes were detected. After quantifying the identified compounds, it was determined that the fat body is the main place of storage and/or production of the cuticular hydrocarbons. It was also observed that the absolute quantity of cuticular hydrocarbons increases progressively during larval development. Inferences about the transport behavior of matured larvae to the pupation place and the colony odor are discussed.
Keywords: Cuticle; Fat body; Gas chromatography; Pachycondyla; Salivary glands; Formicidae; Hymenoptera; Neoponera; Neoponera villosa; Pachycondyla villosa; Ponerinae; Villosa